Complex assessment of the efficiency of granulation process in dispersed systems - Kornienko, Yaroslav; Sachok, Roman (Publishing House of Lviv Polytechnic National University, 2008)
The methodology of complex assessment of the dispersed composition of the granulated product obtained during granulation fromliquid systems for various types of humic and mineral solid composites has been offered. A complex assessment of the granulation process efficiency by granulation coefficient and the quality degradation of the granulated product dispersed composition function has been offered. Запропоновано метод комплексної оцінки дисперсного складу гранульованого продукту, одержаного при гранулюванні з рідких систем для різних типів гуміново-мінеральних багатошарових твердих композитів. Запропонована комплексна оцінка ефективності процесу за коефіцієнтом гранулоутворення та функцією втрат якості дисперсного складу гранульованого продукту.
Комплексна оцінка ефективності процесу гранулоутворення в дисперсних системах
Keywords: dispersed composition; granulation coefficient; quality degradation function; humic-nitrogenous; humic-calcic-nitrogenous; humic-calcic-potassic-nitrogenous multilayer solid composites; дисперсний склад; коефіцієн гранулоутворення; функція втрат якості; гуміново-кальцієво-калійно-азотні багатошарові тверді компоненти; гуміново-азотні; гуміново-кальцієво-азотні